INCREASED DEMAND FOR ALCOHOL AND SMOKING AMONG YOUTH - Jomoliddin Togaymurodov; Sumbula Sharipova (Western European Studies, 2024)
This article discusses the increased demand for alcohol and smoking among young people, smoking habits, complications after smoking, and recommendations. Currently, young people are becoming irresponsible due to their weak willpower. Under the influence of alcohol, people lose their sense of responsibility to society and the state. Restrictions, fines, have been introduced against such situations. The importance of not doing things that contradict the laws and forming strict compliance with them is considered
Keywords: tobacco; alcohol; lawbreaking; health